Postexposition prophylaxis for hepatotropic viruses (HBV and HCV) and human immunodeficiency virus (HIV) - Latković Marina B. (Serbian Medical Society - Dental Section, Belgrade, 2010)
A serious occupational risk of transmitting viral infections caused by hepatotropic viruses, such as hepatitis B virus (HBV) and hepatitis C virus (HCV), and human immunodeficiency virus (HIV) is present in dental practice. The risk of exposure to blood and a variety of pathogenic agents is significantly higher in health care workers. The aim of this study was to present the guidelines in the case of risk contact with potentially infectious material containing hepatotropic viruses (HBV and HCV) and HIV in dental practice. As those viruses cause serious infections, immediately after the exposure (up to 24 hours) it is necessary to visit the referent institution for Postexposition Prophylaxis (PEP) implementation. Complete dental team should be familiar with PEP protocol. PEP should be administered by specialist of infectious diseases who assesses the degree of risk contact. Because of possibly serious complications due to infection by hepatotropic viruses, all health workers should received a vaccine against HBV. Instructions regarding the control testing and counseling are provided by a physician who prescribed PEP. A health worker in Serbia can contact Clinic for Infectious Diseases in Belgrade, Novi Sad and Nis, if PEP is needed.